Toxoplasmosis: morphological and morphometric evaluation of spinal cord neurons from nonsymptomatic seropositive dogs - Carvalho, Alessandra Cristina Francischini de [UNESP]; Pacheco, Maria Rita [UNESP]; Baraldi-Artoni, Silvana Martinez [UNESP]; Girardi, Annita Morais [UNESP] (Universidade Federal de Goiás, 2015)
The aim of this work was to analyze the neuron morphology and morphometry of cervical, thoracic and lumbar areas of nonsymptomatic seropositive dogs’ spinal cord for toxoplasmosis. Twenty indefinite-breed adult dogs were used; ten dogs were healthy, with negative serology for toxoplasmosis, and were used as the control group (group 1), and ten dogs were nonsymptomatic but seropositive for toxoplasmosis (group 2). After the microtomy, with interval of 100 micrometers (µm), the histological 5-µm-thick cuts were dyed by hematoxylin-eosin and Masson's trichrome techniques. The glass slides were analyzed under light microscope to examine the neuron morphology. The parameters considered for the morphometric analysis were area, perimeter, maximum diameter, minimum diameter and shape factor of cytoplasm and nucleus of neuron. The results were statistically analyzed by Student’s t test at 5% probability level. The morphological characteristics between the two groups were similar and according to literature. The morphometric results showed that there were changes in neurons size and structure, and increase and loss of star shape were noticed in seropositive animals. The results suggest that the neurons of these dogs, yet nonsymptomatic, can have lost their conductor function.

Este trabalho objetivou analisar a morfologia e a morfometria dos neurônios das regiões cervical, torácica e lombar da medula espinhal de cães assintomáticos soropositivos para toxoplasmose. Utilizaram-se 20 cães sem raça definida, adultos, sendo dez cães hígidos, com sorologia negativa, utilizados como controle (grupo 1) e dez cães assintomáticos mas soropositivos para toxoplasmose (grupo 2). Após microtomia semi-seriada, com intervalos de 100 micrômetros (µm), os cortes histológicos de medula espinhal, à espessura de 5 µm, foram corados pelas técnicas da hematoxilina-eosina e do tricrômico de Masson. As lâminas foram analisadas à microscopia de luz para verificar a morfologia dos neurônios. Para o estudo morfométrico, os parâmetros analisados foram: área, perímetro, diâmetro máximo, diâmetro mínimo e fator de forma do citoplasma e núcleo dos neurônios. Os resultados obtidos foram analisados estatisticamente, mediante o teste t de Student ao nível de 5% de probabilidade. As características morfológicas entre os dois grupos foram semelhantes e em conformidade com a literatura. Os resultados morfométricos demonstraram que há alteração no tamanho e estrutura dos neurônios, com aumento e perda do formato estrelado nos animais soropositivos. Os resultados sugerem que os neurônios destes cães, ainda que assintomáticos, possam ter perdido sua função condutora.
Toxoplasmose: avaliação morfológica e morfométrica dos neurônios da medula espinhal de cães soropositivos assintomáticos
Keywords: Canine; Central nervous system; Histology; Toxoplasma gondii; Canino; Histologia; Sistema nervoso central; Toxoplasma gondii